FY 2020 Albania Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2022)
The Country Opinion Survey in Albania assists the World Bank Group (WBG)in gaining a better understanding of how stakeholders in Albania perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Albania on 1) their views regarding the general environment in Albania; 2) their overall attitudes toward the WBG in Albania; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Albania; and 4) their perceptions of the WBG’s future role in Albania.